A study of ethical leadership behaviours and integrity system practices from employees' perspectives in Malaysian government-linked companies (GLCs) / Taqiah Hani Muhamad Idris - Muhamad Idris, Taqiah Hani (2019)
In 2017, Malaysia was placed at rank 62 among 180 countries in Corruption Perception Index (CPI) with score of 47 over 100. It was the lowest rank since the index was introduced in 1994. One of the factors that contributed to the lower rank is the increasing of ethics and integrity issues among the top management and leaders in Malaysian Government-Linked Companies (GLCs). This issue has raised the concern of the stakeholders on the need of ethical leaders in GLCs. One of the reasons to have moral and ethical leaders in the management of GLCs is to uphold the level of integrity system of the organization and at the same time to bring positive reputations to the organization. The purpose of this quantitative study was to determine to what extent the influence of ethical leadership behaviours (altruism, courage, ethical guidance, integrity, and fairness) of a leader towards the level of integrity system practices in the organization and to examine the level of integrity system practices in Malaysian GLCs, as perceived by employees. A sample of 305 employees in GLCs participated in completing a survey to address the questions to the ethical behaviours of their leaders and the practice of integrity system in the organization. The mean and Std. deviation analysis indicated the level of integrity system practices in GLCs is at high level at 81.235%. Meanwhile, the Pearson correlation and Multiple regression analysis indicated only altruism behaviour (r = 0.358, p<0.05) and ethical guidance behaviour (r = 0.414, p<0.05) of a leader has positive significant effect towards integrity system practices in Malaysian GLCs. However, in this study it shows that the ethical guidance behaviour of a leader turnout to be the most influencing behaviour towards the level of integrity system practices in GLCs (B = 0.341; t-value = 4.529; p<0.01). These findings are not conclusive as there is no evidence from related study available to support the findings in this study. Future research should include other variables or using moderation or mediation factor in order to analyse other factors influencing the integrity system practices in Malaysian GLCs.